Comfort as "safety-valve" of civilization - Inna Kuzmichenko (Cхід, 2013)
The phenomenon of comfort is considered, his ontological and axiological properties. Paid regard to opposition relations of risk and comfort. As a transmitter of middle potential, explorer and source of culture appearance is offered of hero an inheritance of which is a shove for a desire and possibility of personality to go out outside the area of comfort